Simultaneous Speculation Scheduling - Unger, A.; Ungerer, Th.; Zehendner, E. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 1999)
Simultaneous Speculation Scheduling (S 3 ) is a combined compiler and architecture technique to control multiple path execution. lt can be applied for dual path branch speculation in case of unpredictable branches and for multiple path speculative execution of loop iterations. Loop-carried dependences are handled by data dependence prediction. Architectural requirements are a minimal form of multithreaded processor architecture and three new instructions (fork, sync, wait). Simulation results show performance gains of up to 40% over purely static scheduling techniques by applying the S 3  technique to branches in kernel sections of SPECint95 benchmark programs.